Functions of credit risk - Alimbaev, F. T. (Journal of Economic Research & Business Administration, 2015)
There is a relationship with the bank's credit risk of its revenue. The higher expected income, the higher the credit risk, and conversely, the higher the estimated credit risk of an operation, the greater the profi tability of the bank. Identifying high-risk areas, quantitatively measuring and controlling it regularly, you can manage risk or to prevent them in time. Ignoring or underestimating the credit risk of its functions in the development of tactics and strategies of economic policy making specifi c decisions inevitably hinders economic development.